Avaliação do efeito do processo de secagem do extrato de jenipapo (Genipa americana L.) - Faria, Tenila dos Santos (2019)
Genipap (Genipa americana L.) is a cerrado fruit grown in several regions of Brazil and other countries. It presents 12.05% of peel, generating a large amount of residue after its processing. However, in its composition can be found important bioactive compounds (genipin, geniposide, β-sitosterol), which act as antidiarrheal, antiulcer, analgesic, anti-gonorrhea, and controlling anemia and jaundice. However, such compounds have low heat stability, being susceptible to degradation and oxidation when they are subjected to a thermal process such as drying. The objective of this study was to evaluate the effects of the spray drying and freeze-drying processes of the pulp and peel extract from in natura genipap obtained by different extraction conditions in relation to the content of phenolic compounds and antioxidant activity, as well as, to evaluate the use of the genipap peel as a clarifying agent. Therefore, extraction methods were tested using ultrasonic bath, ultrasonic probe and shaker varying the temperature (40, 60, 70, 80 and 90 °C). From the results, a higher concentration of phenolic compounds present in the genipap pulp was verified from the extraction by ultrasonic probe at 40 °C, 11.05 ± 0.08 mgGAE/g of genipap pulp, indicating the efficiency of the application of the waves directly in the sample. Regarding the peel, the best method was using the shaker at 80 °C, 9.71 ± 0.03 mgGAE/g of genipap peel. Analyzes of antioxidant activity showed that the conditions were efficient in the extraction process resulting in the extraction and preservation of the active compounds. For clarification aqueous solutions of clarifying agent were added and added to the extract of genipap varying the final concentrations of 100 to 10,000 mg/L. For the procedure the genipap peel with and without lignin was used, as well as, chitosan as a comparison. To verify the influence of pH on the improvement of the clarification process, acidified solutions of lignin and lignin-free peel and chitosan were also used. Each sample was analyzed for total solids content, total phenolic compounds and pH, and the best condition was for acidified peel without lignin at 100 mg/L. Spray drying was performed using the extract of the genipap pulp with and without addition of maltodextrin as adjuvant, comparing the drying in freeze-drier. The samples were analyzed for the content of phenolic compounds and antioxidant activity. As a result, it was observed that the use of maltodextrin had a great influence on the drying in spray dryer contributing to the quality of the dried product by reducing its hygroscopicity. However, higher concentrations of adjuvants had lower levels of phenolic compounds as well as antioxidant activity, being the best condition in spray dryer at 90 °C and concentration of 40% maltodextrin, and in freeze-drier at 100 °C and 35.7% of adjuvant. Therefore, the best extraction of phenolic compounds from in natura genipap pulp was using the ultrasonic probe at 40 °C and the shaker was used at 80 °C for the peel. In addition, the use of the genipap peel after the removal of the lignin proved to be a good alternative as a clarifying agent from the concentration of 100 mg/L in acidified solution. It was also verified that the use of maltodextrin in the drying process contributed to decrease the hygroscopicity of the sample, preventing it from sticking to the wall of the equipment, as well as, preserving the content of phenolic compounds and antioxidant activity.